Strategic Marketing Management: Building a Foundation for Your Future: FE299/FE299, 10/2015 - Wysocki, Allen F.; Wirth, Ferdinand F.; Farnsworth, Derek; Clark, Jennifer (EDIS, 2015)
This document is about helping firms and individuals understand the implications of a strategic marketing management program. It introduces the basics of a marketing plan and the importance of performing a SWOT analysis to identify strengths, weaknesses, opportunities, and threats. The workbook emphasizes the need for external and internal analysis to form effective strategies, improve efficiency, and increase profitability. It also highlights the importance of customer, competitor, and industry analysis in crafting a strategic marketing plan. First published Sept. 2001.